Kegigihan dan Subjective Well Being Pada Mahasiswa Pekerja Part Time - Syah Dwi Puspita Ningrum; Irfani Rizal; Leni Armayanti; Nindy Amita (Psychopolytan : Jurnal Psikologi, 2025)
Working students often face limited time to complete assignments, which increases stress and affects their subjective well-being (SWB). Kegigihan, reflecting high levels of perseverance and consistency, is assumed to play a role in enhancing SWB. This study aims to analyze the relationship between kegigihan and SWB among part-time working students at Universitas Islam Riau. The sample consisted of 103 students selected through purposive sampling. Kegigihan was measured using the Oviedo Kegigihan Scale (10 items), while SWB was assessed with the Satisfaction with Life Scale (5 items) and the Scale of Positive and Negative Experiences (20 items). The findings revealed a significant positive relationship between kegigihan and SWB (r = 0.383, p < 0.05), with kegigihan contributing 42.7% to SWB. These results suggest that kegigihan can be an important factor in improving the subjective well-being of part-time working students.